Small Assignment Sheet - Westervelt, Saundra (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
You must turn in a total of FOUR small papers during the semester. Two of these assignments are non-negotiable: everyone must do them. For the other two assignments, I have given you a number of "think" questions throughout the semester; you can choose any TWO of these to write on. In several cases, adequate responses to these optional paper questions will require you to read the recommended readings for that topic. All of these assignments are designed to prompt you to think critically about the material we are covering in class and in the readings.